The Role of Taxes in Economic Development of Kosovo - Nimani, Artan (European Journal of Economics and Business Studies, 2016)
To achieve prosperity and political stability, national governments aimed at achieving economic equilibrium. The government uses various instruments to stimulate economic growth, reduce unemployment and to achieve macroeconomic objectives. In the context of slow economic growth in recent years and fiscal pressures, Kosovo faces the complex challenge of economic development. Unemployment remains at a high level. Demand for labor is still very low and create an environment that will favor the formation of stable work places is a challenging task that requires a multidimensional reforms in the economy. This paper addresses the impact of fiscal policy on reducing unemployment, increasing investment and consumption to generate sustainable economic growth.
Keywords: fiscal policy, unemployment, investment, consumption, economic growth